Penerapan Metode Basis Path Analysis dalam Pengujian White Box Sistem Pakar - Cindy Pamela C Munaiseche; Gladly C Rorimpandey (Ikatan Ahli Informatika Indonesia, 2021)
Testing is an important thing to do for a software. Early stage testing can be done through unit testing. The unit testing uses whitebox testing with the basis path analysis method. This method using the program structure from a flowchart program and then it will be converted into a flowgraph, but actually there are so much program code that is divided into many files that do not allow for flowgraphs to be created. This research aims to apply the basis path analysis method for the white box testing in the expert system of diagnosing heart disease by using the flowchart system to overcome the problem of the number of program code files that resulted in the difficulty of making flowgraphs. The Basis Path Analysis method consists of four stages, namely: flowgraph creation, calculation of cyclomatic complexity (CC), independent path determination, and finally test case testing. The test results showed that the system procedures were more complex with the risk level being at medium levels and all the tested pathways in the form of test cases were appropriate. This research contribution is expected to help software developers in testing whitebox by using flowchart system.